Peran Kualitas Produk, Online Customer Review, Dan Customer Rating Terhadap Keputusan Pembelian Produk Kecantikan Pada Tiktokshop - Lisa Ayu Pransiska; Sumartik Sumartik; Herlinda Maya Kumala Sari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of product quality, online customer reviews and customer ratings on purchasing decisions for beauty products on Tiktok. This study uses a quantitative approach. The sampling technique used was non-probability sampling with the accidental sampling method with a total of 100 respondents. The data collection technique was carried out by distributing questionnaires. The data analysis technique uses Partial Least Square (PLS) with the Smart-PLS version 4.0 program. The results of this study indicate that Product quality influences the decision to purchase Somethink products. Online Customer Reviews have an effect on the decision to purchase Somethink products. Customer Rating influences the decision to purchase Somethink products. Keywords – Product Quality, Online Customer Reviews, Customer Ratings, Purchasing Decisions